The secret scripture - Barry, Sebastian, 1955- (Penguin Books, 2009)
As a young woman, Roseanne McNulty was one of the most beautiful and beguiling girls in County Sligo, Ireland. Now, as her hundredth year draws near, she is a patient at Roscommon Regional Mental Hospital, and she decides to record the events of her life. As Roseanne revisits her past, hiding the manuscript beneath the floorboards in her bedroom, she learns that Roscommon Hospital will be closed in a few months and that her caregiver, Dr. Grene, has been asked to evaluate the patients and decide if they can return to society. Roseanne is of particular interest to Dr. Grene, and as he researches her case he discovers a document written by a local priest that tells a very different story of Roseanne's life than what she recalls. As doctor and patient attempt to understand each other, they begin to uncover long-buried secrets about themselves.